Spatial quantification of leafless canopy structure in a boreal birch forest - Reid, Tim; Spencer, Michael; Huntley, Brian; Hancock, Steven; Essery, Richard; Carle, Joel; Holden, Robert; Baxter, Robert; Rutter, Nick (Agricultural and Forest Meteorology, 2014)
Leafless deciduous canopies in boreal regions affect the energy available for snowmelt and reduce over-all surface albedo during winter, thereby exerting a strong influence on weather and climate. In this work, ground-based measurements of leafless canopy structure, including hemispherical photography, terrestrial laser scanning (TLS) and manual tree surveys were collected at 38 sites in an area of mountain birch forest in northern Sweden in March 2011 and 2012. Photo-derived sky view fraction was strongly inversely correlated (r < −0.9) to the total tree basal area in a 5 m radius around the photo site. To expand findings to wider areas, maps of canopy height for a 5 km × 3 km area were obtained from airborne lidar (ALS) data collected during summer 2005. Canopy heights derived from TLS were used to validate the ALS estimates, and simple models were developed to establish relationships between hemispherical sky view and ALS canopy height (RMSE < 5%). The models and ALS data provide useful methods for estimating canopy radiative transfer and biomass over wide areas of birch forest, despite the relatively low ALS resolution (∼1 return m−2).